Efficacy and safety of percutaneous ASD closure in adults: comparative outcomes of occluder devices in a single-center cohort - Kayvanpour, Elham; Matzeit, Elena; Reich, Christoph; Kaya, Ziya; Pleger, Sven Torsten; Frey, Norbert; Meder, Benjamin; Sedaghat-Hamedani, Farbod (Journal of Clinical Medicine, 2025)
Background: Atrial septal defect (ASD) is a prevalent congenital heart condition, resulting in left-to-right shunting. Untreated ASDs may be associated with complications, including right-sided heart failure, pulmonary hypertension, and atrial arrhythmias. Percutaneous ASD closure, performed with various occluder devices, has become the preferred approach for symptomatic patients with suitable anatomy, yet data on device-specific efficacy and safety profiles remain limited. Methods: This study was a retrospective, single-center analysis involving patients who underwent percutaneous ASD closure between January 2000 and February 2023. Data on patient characteristics, indications for the procedure, procedural details, and clinical outcomes were extracted from electronic medical records. Endpoints included complications at the puncture site, pericardial effusion, atrial arrhythmias, device-related thrombus formation, and overall survival. Results: A total of 195 patients were included (mean age 53.6 ± 16.2 years; 60.5% female). Three different devices were used: Amplatzer ASD occluder (n = 111), Gore Septal Occluder (n = 67), and Occlutech ASD occluder (n = 17). Initial procedural success rate was 90.8%, with no significant differences observed between devices. Periprocedural complication rates were low and comparable across all devices. New-onset atrial fibrillation within the first month post-implantation occurred in 7.5% of patients with the Gore device, compared to 0.9% with the Amplatzer device (p = 0.03) and 0% with the Occlutech device. No statistically significant differences were observed among the devices regarding thrombus formation, late-onset pericardial effusion, device erosion, or stroke. Conclusions: Percutaneous ASD closure demonstrates high procedural success and low complication rates across different occluder devices, supporting its efficacy and safety as a treatment for adults. Although the Gore device showed a higher incidence of new-onset AF compared to the Amplatzer device, no significant differences were observed regarding thrombus formation, pericardial effusion, device erosion or stroke.
Gesehen am 10.07.2025